Taxpayer Awareness, Taxpayer Socialization, and Tax Sanctions on Taxpayer Compliance in Paying Land and Building Tax in Bekasi Regency - Benny Oktaviano; Tirin Wulandari; Erlina Widayanti (East Asian Journal of Multidisciplinary Research, 2023)
Land and Building Tax is an important source of income for each region; therefore, each local government has its own way to optimize local revenue from the Land and Building Tax sector. This study aims to analyze the effect of awareness, socialization, and sanctions on taxpayer compliance in paying land and building tax in Bekasi Regency, both simultaneously and partially. This research was conducted on PBB taxpayers in Bekasi Regency with the following numbers: The sample used in this study was 100 taxpayers using a simple random sampling technique, and the data analysis technique used multiple linear regression. The test results of this study show that the variables of awareness and socialization have a significant effect on taxpayer compliance in paying land and building taxes, while the sanctions variable has no effect on taxpayer compliance in paying land and building taxes.